Nuclear magnetic resonance of biological macromolecules. - James, Thomas L.; Dotsch, Volker; Schmitz, Uli (Methods in enzymology, 2001)
This volume and its companion, Volume 338, supplement Volumes 176, 177, 239, and 261. Chapters are written with a "hands-on" perspective. That is, practical applications with critical evaluations of methodologies and experimental considerations needed to design, execute, and interpret NMR experiments pertinent to biological molecules